2019
DOI: 10.1186/s12876-019-0985-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of moderate to severe irritable bowel syndrome with constipation in six European countries

Abstract: Background Irritable bowel syndrome with predominant constipation (IBS-C) is a complex disorder with gastrointestinal and nervous system components. The study aim was to assess the economic burden of moderate to severe IBS-C in six European countries (France, Germany, Italy, Spain, Sweden and the UK). Methods An observational, one year retrospective-prospective (6 months each) study of patients diagnosed in the last five years with IBS-C (Rome III criteria) and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 36 publications
0
69
0
3
Order By: Relevance
“…The direct cost EUR 4,282 can be compared with data published by the Swedish Association of Local Authorities and Regions, wherein they reported an annual healthcare direct cost of EUR 1,951 for an average female Swede. Our total annual cost of EUR 8,768/woman can also be compared with other recent Swedish studies reporting annual costs in other benign persistent conditions: annual total cost of migraine was EUR 10,790 (EUR rate 2013) per patient [22], annual total cost of Irritable bowel syndrome with predominant constipation was EUR 12,873 (EUR rate 2019) per patient [23], and mean total cost of low back pain was EUR 2,753 (EUR rate 2016) per episode [24].…”
Section: Discussionmentioning
confidence: 71%
“…The direct cost EUR 4,282 can be compared with data published by the Swedish Association of Local Authorities and Regions, wherein they reported an annual healthcare direct cost of EUR 1,951 for an average female Swede. Our total annual cost of EUR 8,768/woman can also be compared with other recent Swedish studies reporting annual costs in other benign persistent conditions: annual total cost of migraine was EUR 10,790 (EUR rate 2013) per patient [22], annual total cost of Irritable bowel syndrome with predominant constipation was EUR 12,873 (EUR rate 2019) per patient [23], and mean total cost of low back pain was EUR 2,753 (EUR rate 2016) per episode [24].…”
Section: Discussionmentioning
confidence: 71%
“…Further investigation is needed to determine the prevalence and relevance of the range of functional gastrointestinal disorders in patients with fibromyalgia. 3 Background Both functional gastrointestinal disorders (FGID) and fibromyalgia are poorly understood syndromes significantly impacting quality of life (1) and imposing substantial financial burden (2, 3) with healthcare-associated costs reaching quadruple that of a reference population (4). Both syndromes are considered attributable to sympathetic dysfunction (5) resulting in central sensitisation (6) and were recently categorised as "Central Sensitivity Syndromes" (7,8).…”
Section: Resultsmentioning
confidence: 99%
“…7 In two independent studies it were estimated that Open access IBS-related absenteeism and presenteeism cost industry £400-£900 8 or to €937-€2108 annually. 9 A diet that is low in fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) 10 alias a low FODMAP diet (LFD), is an effective dietary intervention for IBS. A blinded and placebo-controlled trial found that approximately three-quarters of patients with IBS benefit from an LF.…”
Section: Introductionmentioning
confidence: 99%